2016
DOI: 10.1094/phyto-12-15-0322-r
|View full text |Cite
|
Sign up to set email alerts
|

Rice Bran Amendment Suppresses Potato Common Scab by Increasing Antagonistic Bacterial Community Levels in the Rhizosphere

Abstract: Potato common scab (PCS), caused by pathogenic Streptomyces spp., is a serious disease in potato production worldwide. Cultural practices, such as optimizing the soil pH and irrigation, are recommended but it is often difficult to establish stable disease reductions using these methods. Traditionally, local farmers in southwest Japan have amended soils with rice bran (RB) to suppress PCS. However, the scientific mechanism underlying disease suppression by RB has not been elucidated. The present study showed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 59 publications
2
12
1
Order By: Relevance
“…This was not expected, as the last three families were more prevalent in CS conducive than suppressive soil in Michigan (8). Our Illumina sequencing indicated that Rhizobiales and Planctomycetales were enriched in suppressive soil, as in Cha et al (29), but Actinobacteria, Chloroflexi, Bacillaceae , and Chitinophagaceae that increased with CS suppressiveness induced by rice bran (22) were more prevalent in the conducive soil here. Therefore, different biocontrol consortia may be at work in different types of suppressive soils.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…This was not expected, as the last three families were more prevalent in CS conducive than suppressive soil in Michigan (8). Our Illumina sequencing indicated that Rhizobiales and Planctomycetales were enriched in suppressive soil, as in Cha et al (29), but Actinobacteria, Chloroflexi, Bacillaceae , and Chitinophagaceae that increased with CS suppressiveness induced by rice bran (22) were more prevalent in the conducive soil here. Therefore, different biocontrol consortia may be at work in different types of suppressive soils.…”
Section: Discussionsupporting
confidence: 66%
“…Further to that the quantity of pathogenic streptomycetes (based on numbers of txtB genes) did not change with soil suppressiveness or cultivar in tuberosphere and bulk soil, but in suppressive soil the number of pathogens decreased in potato periderm possibly due to both microbial interactions and soil chemical conditions depending on location (9, 21). In this study, however, the increased numbers of actinobacteria in periderm of susceptible cultivar did not correspond to pathogenic streptomycetes, so perhaps an antagonistic community of actinobacteria developed there as a response to pathogen infection, similarly as in Rosenzweig et al (8) or Tomihama et al (22).…”
Section: Discussioncontrasting
confidence: 46%
“…The effect of bioagents on the α-diversity of plant-related microbial communities varies. Some studies indicate that application of bioagents can increase the α-diversity of the bacterial rhizosphere community [ 11 , [27] , [28] , [29] ], while another study reported that the application of a rice bran amendment suppressed PCS and resulted in a significant decrease in the α-diversity of the rhizosphere bacterial community [ 30 ]. It is possible that a higher bacterial α-diversity does not necessarily lead to a lower incidence of plant disease.…”
Section: Resultsmentioning
confidence: 99%
“…Bacterial taxa in the Burkholderiales have been recently reported to be plant growth-promoting rhizobacteria (PGPR) that stimulate plant growth [ 38 ]. Bioagents in the genus, Pseudomonas , also have the potential to reduce the incidence of PCS under field conditions [ 16 , 30 ]. Collectively, our results indicate that application of the designated microbial product contributes to an increase in the relative abundance of beneficial bacteria in the rhizosphere of potato.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation